Enhancing Travel Recommendations Through Attraction Preference Standardization - Saketha, N.; Chitra, K. (INTI International University, 2024)
The subsequent paper describes a typical travel recommendation system that comprises collaborative filtering, content-based filtering, and sentiment analysis in its design. The proposed system enhances the problems of conventional methods by using operation preferences to standardize attraction and adopting sentiments obtained from the rating. The following are the steps of the implementation of the study; data collection, data pre-processing, data modelling and the last is the development of web application. Actual analysis proves that there was a general enhancement in the precision of the recommendation and also the satisfaction level of the customers.